ADAMTS-13 Activity Predicts Outcome in Acute Ischaemic Stroke Patients Undergoing Endovascular Treatment - Schuppner, Ramona; Dirks, Meike; Grosse, Gerrit M.; Böckmann, Matthias; Goetz, Friedrich; Pasedag, Thomas; Bode-Böger, Stefanie M.; Martens-Lobenhoffer, Jens; Budde, Ulrich; Lanfermann, Heinrich; Lichtinghagen, Ralf; Weissenborn, Karin; Worthmann, Hans (Thrombosis and Haemostasis, 2018)
Background Endovascular treatment improves outcome in patients with acute ischaemic stroke due to large vessel occlusion in general. But outcome in some of these patients is jeopardized by recanalization failure or bleeding.Objectives This study aimed to determine a possible association of mediators of inflammation and haemostasis (C-reactive protein, interleukin-6, matrix metalloproteinase-9, monocyte chemoattractant protein-1, asymmetric dimethylarginine [ADMA], symmetric dimethylarginine, von Willebrand factor and a disintegrin and metalloproteinase with a thrombospondin type 1 motif 13 [ADAMTS-13]) with the post-intervention grade of reperfusion, complications and clinical outcome in patients who underwent endovascular treatment of ischaemic stroke.Patients/Methods Forty-one patients with acute ischaemic stroke due to large vessel occlusion were prospectively enrolled into the study. Peripheral venous blood was taken prior to treatment and 24 hours and 3, 7 and 90 days after symptom onset. The post-intervention grade of reperfusion was determined using the modified Treatment in Cerebral Infarction (mTICI) score. Clinical outcome on day 90 was assessed using the modified Rankin's scale (mRS).Results Low ADAMTS-13 activity (p = 0.009) and missing of statin therapy (p = 0.038) on admission were independently associated with unfavourable outcome (mRS: 5–6). Patients with unsuccessful reperfusion (mTICI: 0–1) showed higher ADMA levels on admission (p = 0.018). However, this association could not be confirmed in the binary logistic regression analysis.Conclusion Low ADAMTS-13 activity is a predictor of unfavourable outcome in patients with ischaemic stroke undergoing endovascular therapy. Further studies are warranted to elucidate the clinical and potential therapeutic role of ADAMTS-13 in acute ischaemic stroke.
Keywords: thromboinflammation; endovascular therapy; acute ischaemic stroke